2006
DOI: 10.1111/j.1745-4573.2006.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Species in Meat and Meat Products Using Enzyme‐linked Immunosorbent Assay

Abstract: Detection of species adulteration in meat products is important for consumer protection and food labeling law enforcement. In this study, samples of 28 fermented sausages; 14 cooked salami; 11 frankfurters; 9 raw meats; 16 raw ground meats and meat balls; 3 pastramis, 2 hams and 5 bacons; 7 cooked meats; and 5 canned products resulting in a total of 100 meat and meat products were analyzed for species determination by enzyme-linked immunosorbent assay test kits prepared with monoclonal antibody technique. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
62
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 14 publications
(14 reference statements)
5
62
1
4
Order By: Relevance
“…Apart from the potential for cross contamination, an explanation for the high incidence of this undeclared species in the aforementioned products could have been due to the substitution of cheaper chicken flesh or fat for more expensive beef or mutton constituents, or alternatively due to the unacknowledged incorporation of chicken MRM (Hsieh, Johnson,Wetzstein, & Green,1996). Similar reports on the detection of undeclared poultry in ground meat products from Alabama and Turkish markets have been documented in the literature (Ayaz et al, 2006;. Surprisingly, since chicken was found to be widely used as an ingredient in deli meats and because species substitution could be easily masked in such highly comminuted products, only two samples within this category tested positive for undeclared chicken (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Apart from the potential for cross contamination, an explanation for the high incidence of this undeclared species in the aforementioned products could have been due to the substitution of cheaper chicken flesh or fat for more expensive beef or mutton constituents, or alternatively due to the unacknowledged incorporation of chicken MRM (Hsieh, Johnson,Wetzstein, & Green,1996). Similar reports on the detection of undeclared poultry in ground meat products from Alabama and Turkish markets have been documented in the literature (Ayaz et al, 2006;. Surprisingly, since chicken was found to be widely used as an ingredient in deli meats and because species substitution could be easily masked in such highly comminuted products, only two samples within this category tested positive for undeclared chicken (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Thus, if cross contamination was the reason for the presence of undeclared species in deli meats, it would be expected that the latter number would be higher given the extensive inclusion of chicken in such products. In contrast to these findings, Ayaz et al (2006) found that poultry was the major undeclared species in deli meats collected from Turkey, where 5 of 13 (38%) cooked beef salami samples and 3 of 11 (27%) beef frankfurters tested positive for the presence of poultry. In addition, these authors reported on the complete substitution of poultry meat for beef in 11 of 24 (46%) fermented sausage products.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…The results showed that 22.0% of the samples were not in compliance with Turkish Food Codex, violating consumer rights and presenting a potential public health risk. [4] However, using an ELISA it is difficult to analyze different species in a single run, and also is quite expensive. [3] PCR methods are widely applied to identify meat species in routine laboratories.…”
mentioning
confidence: 99%